Kinetic features and characterization of liver glutathione transferase in rats exposed to glyphosate - Olawale Moses Oyewole; Oluwatosin Adebisi Dosumu; Olusegun Mark Obafemi Idowu; Tope Gafar Atere; Abiola Muhammad Adeosun; Oluseyi Adeboye Akinloye (BIORE Scientia Publisher, 2025)
Glutathione-S-transferases (GSTs) are phase-II metabolizing enzymes which detoxify various compounds through their conjugation reaction. This study characterized and investigated the kinetic properties of liver glutathione-S-transferase in rats exposed to glyphosate. Rats of average weight 200 g were randomly divided into groups (n=4); A, B, C and D. Group A served as control and received distilled water alone while groups B, C and D were exposed to 200, 300 and 400 mg/kg body weight of glyphosate respectively. Three GST model substrates [1, 2-dichloro-4-nitrobenzene (DCNB), paranitrobenzylchloride (pNBCl), and 1-chloro-2, 4-dinitrobenzene (CDNB)] were used to determine the substrate utilization pattern of the GST isozymes in the liver crude homogenate. The liver homogenate was purified by combination of 80 % ammonium sulfate precipitation, gel filtration chromatography on Sephacryl S-200 column and ion exchange chromatography on CM-Sepharose column. Spectrophotometric methods were used to determine the activity of the GSTs and protein concentration. GST isozymes in the liver homogenate were unable to conjugate pNBCl to GSH, DCNB showed slight conjugation while CDNB shows a 2-fold conjugation. The optimum temperature for the induced isozymes of GST A and GST B were 400C and 500C respectively while the optimum pH were 8.0 and 8.5 respectively. In this study, pNBCl proved unsuitable due to its inability to conjugate GSH. Future study may provide additional information about the class of GST isozyme induced.